Não-preferência para oviposição de traça-das-crucíferas em genótipos de couve-flor - Boiça Júnior, Arlindo Leal [UNESP]; Filho, Norton Rodrigues Chagas; de Souza, Joseane Rodrigues [UNESP] (My University, 2010)
The Diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), is one of the main plague-insect specie of Brassicaceae plants in Brazil and all over the world. The resistant genotypes use to its control is a promising alternative. This work aimed evaluates the eggs distribution along the plant, the adults' density per plant, and determine the cauliflower genotypes effect in the P. xylostella oviposition. The experiment was carried out at FCAV/UNESP-Jaboticabal Campus Phytossanity Department (Departamento de Fitossanidade). It was evaluated the eggs distribution, the P. xylostella adults density effect using Sharon hybrid, and tests with or without choose choice to determine the P. xylostella nonpreference in the Teresópolis Gigante, Verona, Barcelona, Sharon, Silver Streak, and Piracicaba Precoce genotypes. It is possible conclude that P. xylostella has higher willingness to oviposits in the stem than in the basal leaves. The three couple density of P. xylostella per plant is the best to discriminate cauliflower genotypes regarding the resistance grade to nonpreference choose choice to oviposition. During the P. xylostella oviposition preference tests with choose choice, the genotypes Sharon, Piracicaba Precoce, Barcelona, Verona e Teresópolis Gigante are less desirable to oviposition; while during the no choose choice tests the genotypes did not differ among them.
Diamondback moth oviposition nonpreference in cauliflower genotypes
Keywords: Brassicaceae; Insecta; Plutella xylostella; Resistance types